Procalcitonin in sepsis and bacterial infections - Abhijit Chaudhury; G.L. Sachin Sumant; R. Jayaprada; Usha Kalawat; B.V. Ramana (Journal of Clinical and Scientific Research, 2013)
The differentiation of sepsis and systemic bacterial infections from other causes of systemic inflammatory response is crucial from the therapeutic point of view. The clinical signs and symptoms are non-specific and traditional biomarkers like white cell count, erythrocyte sedimentation rate and C-reactive protein are not sufficiently sensitive or specific to guide therapeutic decisions. Procalcitonin (PCT) is considered a reliable marker for the diagnosis and prognosis of moderate to severe bacterial infections, and it has also been evaluated to guide the clinicians in the rational usage of antibiotics. This review describes the diagnostic and prognostic role of PCT as a biomarker in various clinical settings along with the laboratory aspects and its usefulness in risk stratification and antibiotic stewardship.